Pressure injection of calcium both excites and adapts Limulus ventral photoreceptors (The Rockefeller University Press, 1986)
Single pressure injections of 1-2 mM calcium aspartate into the light- sensitive region of Limulus ventral photoreceptors resulted in a rapid, 20-40-mV depolarization lasting approximately 2 s. The depolarization closely followed the rise in intracellular free calcium caused by the injection, as indicated by aequorin luminescence. The depolarization was followed by reversible desensitization (adaptation) of responses to both light and inositol 1,4,5 trisphosphate. Similar single injections of calcium into the light-insensitive region of the receptor were essentially without effect, even though aequorin luminescence indicated a large, rapid rise in intracellular free calcium. The depolarization caused by injection of calcium arose from the activation of an inward current with rectification characteristics and a reversal potential between +10 and +20 mV that were similar to those of the light- activated conductance, which suggests that the same channels were activated by light and by calcium. The reversal potentials of the light- and calcium-activated currents shifted similarly when three-fourths of the extracellular sodium was replaced by sucrose, but were not affected by a similar replacement of sodium by lithium. The current activated by calcium was abolished by prior injection of a calcium buffer solution containing EGTA. The responses of the same cells to brief light flashes were slowed and diminished in amplitude, but were not abolished after the injection of calcium buffer. Light adaptation and prior injection of calcium diminished the calcium-activated current much less than they diminished the light-activated current.